Comparison between Quantitative Computed Tomography and Dual-Energy X-Ray Absorptiometry in the Detection of Osteoporosis in Postmenopausal Women - Abdulsattar Hameed Hammood; Sahar Basim Ahmed; Hassan, Qays Ahmed (AL-Kindy College Medical Journal, 2023)
Background: Osteoporosis is denoted by low bone mass and microarchitectural breakdown of bone tissue, directing to increased fracture risk and bone fragility. Fractures may lead to a decreased quality of life and increased medical costs. Thus, osteoporosis is widely considered a significant health concern.Objective. This study aimed to compare quantitative computed tomography (QCT) and dual-energy X-Ray absorptiometry (DXA) to detect osteoporosis in postmenopausal women.Subjects and Methods. We measured spinal volumetric bone mineral density (BMD) with QCT and areal spinal and hip BMD with DXA in 164 postmenopausal women. We calculated the osteopenia and osteoporosis detection rate for the two methods. The difference between these rates for DXA versus QCT was analyzed using the chi-square test.Results. The detection rate of osteoporosis was 57.9% for QCT and 50.6% for DXA (significant difference, p=0.002). At the same time, the detection rate of osteopenia was 36.6% for QCT and 31.7% for DXA (significant difference, p=0.002).Conclusions. Quantitative CT bone densitometry is an excellent tool for the evaluation of BMD. It is more sensitive than DXA for detecting osteoporosis in postmenopausal women.